The Effectiveness of Group Therapy based on Mentalization and Dialectical Behavior on Clinical Symptoms of Borderline Personality Disorder: A randomized controlled clinical trial - Leila Khabir; Nurollah Mohamadi; Changiz Rahimi; Seyed Ali Dastgheib (Shiraz University of Medical Sciences, 2018)
Background: Dialectical Behavior Therapy (DBT) and Metalization-based Treatment (MBT) are two approaches to the treatment of Borderline Personality Disorder (BPD). The present study aimed to investigate the clinical outcomes of dialectical behavior group therapy and metallization-based group therapy on reduction of the severity of symptoms in patients with BPD. Methods: This is a single-blind randomized controlled clinical trial conducted on 36 patients diagnosed with BPD by a psychiatrist. They were examined by a semi-structured clinical interview. Data were collected from March 2017 to June 2017. The participants were categorized into intervention and control groups. Before, immediately and two months after the intervention, the participants filled out the Borderline Personality Disorder Severity Index (BPDSI), Beck Anxiety Inventory (BAI), and Beck Depression Inventory-II (BDI-II) questionnaires. Results: The two group therapy based on MBT and DBT were effective in reducing the symptoms of borderline personality disorder equally (p=0.4). Both treatments were more effective than the control group receiving only medication (p<0.001).  This improvement was persistent two months after the intervention (p<0.001). Conclusion: The results of the study revealed that group psychotherapy based on metallization and dialectical behavior combined with pharmacotherapy is considerably more effective than treatment with pharmacotherapy. Metallization can be a common factor in any successful treatment of BPD.